2021
DOI: 10.1101/2021.04.02.21254514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of COVID-19 severity and immune response in the respiratory tract microbiome

Abstract: Rationale: Viral infection of the respiratory tract can be associated with propagating effects on the airway microbiome, and microbiome dysbiosis may influence viral disease. Objective: To define the respiratory tract microbiome in COVID-19 and relationship disease severity, systemic immunologic features, and outcomes. Methods and Measurements: We examined 507 oropharyngeal, nasopharyngeal and endotracheal samples from 83 hospitalized COVID-19 patients, along with non-COVID patients and healthy controls. Ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The main characteristics of the studies are shown in Tables 2 , 3 , 4 . Ten studies investigated the association between gut microbiota and COVID-19 [ 26 35 ], 11 studies investigated the association between airway microbiota and COVID-19 [ 36 46 ] and one study investigated the association between both gut and airway microbiota and COVID-19 [ 47 ]. All studies collected their samples after onset of infection with SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics of the studies are shown in Tables 2 , 3 , 4 . Ten studies investigated the association between gut microbiota and COVID-19 [ 26 35 ], 11 studies investigated the association between airway microbiota and COVID-19 [ 36 46 ] and one study investigated the association between both gut and airway microbiota and COVID-19 [ 47 ]. All studies collected their samples after onset of infection with SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…The search identified 10 cohort studies [ 36 43 , 45 , 46 ] and one case–control study [ 44 ] investigating the association between airway microbiota and COVID-19 (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of secondary infections is generally anticipated, albeit the frequency of the same could be variable. Such perturbation is also evident during COVID-19 as shown through molecular epidemiological studies of the upper respiratory microbiome [115][116][117]. Admission to healthcare centers carries with it the opportunity for nosocomial infections.…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%
“…There have been several studies examining correlations between the URT microbiota and SARS-CoV2 infection since the beginning of the COVID-19 global pandemic. These studies indicate that the microbiota is shifted with an enrichment of pathobionts and opportunistic pathogens in COVID-19 patients compared to non-infected individuals (Engen et al, 2021;Merenstein et al, 2021;Rhoades et al, 2021). We note that at the time of writing, some of these studies have not yet been peer reviewed.…”
Section: Adenovirus/coronavirusmentioning
confidence: 99%